Structure of the thermo-sensitive TRP channel TRP1 from the alga Chlamydomonas reinhardtii - Luke L. McGoldrick; Appu K. Singh; Lusine Demirkhanyan; Ting-Yu Lin; Ryan G. Casner; Eleonora Zakharian; Alexander I. Sobolevsky (Nature Communications, 2019)
Transient receptor potential (TRP) channels are ubiquitous occurring cation-selective sensory ion channels that respond to various stimuli. Here the authors characterize crTRP1 from the alga Chlamydomonas reinhardtii, present its 3.5 Å cryo-EM structure and show that crTRP1 opens in response to increased temperature and is positively regulated by the membrane lipid PIP2.